Development of mobile learning-based learning media on the distribution and management of natural resources - Irmansyah, Kevin Ian; Soelistijo, Djoko; Rosyida, Fatiya; Wirahayu, Yuswanti Ariani (PT. Pena Produktif Kreatif, 2025)
Natural resource material in geography subjects is real, conceptual, and related to the environment around students. Therefore, it is necessary to develop media that supports these needs. This is in accordance with the results of the analysis of student needs which is known as many as 15 students need learning media in the form of mobile applications. The development of mobile applications in this study is based on the analysis of the weaknesses of the previous media which only presents material conceptually. Through the analysis of these needs, it is necessary to develop mobile learning-based learning media on the distribution and management of natural resources. This development research aims to produce learning media based on mobile learning on the distribution and management of natural resources. This development research applies to the ADDIE model with four stages, including analysis, design, development, and evaluation. The product development results are in the form of an html file and an android apk named NARESa. The advantages of this learning media product are that it has an attractive appearance, is easy to use in the learning process, and presents contextual material. Suggestion from media expert validator is to add developer identity. Suggestions from material expert validators are that it is necessary to add sustainable principles and to add concept maps. The media feasibility test was carried out in class XI students of SMAN 7 Malang. Based on the results of the feasibility test, the media got a score of 84% with qualifications suitable for use. Suggestions for further research are the development of learning media that does not depend on an internet connection, so it is not slow in opening the existing features.